Porous film for energy storage device separators, ion exchange membrane support, and energy storage device
Patent Information
- Application Number
- JP2025057796
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0016】 本発明によれば、多孔フィルムを製造する際、特に樹脂組成物を溶融押出してペレットを作製する際に目ヤニの発生を抑制することができ、さらには、そのようなペレットを使用することにより、フィルム製膜時での目ヤニを低減することができ、安定して長くフィルムを製造することができる。さらに本発明の蓄電デバイスセパレータ用多孔フィルムは、薄膜でありながら、透気特性も良好な蓄電デバイスセパレータ用多孔フィルムを得ることができる。 よって、本発明の蓄電デバイスセパレータ用多孔フィルムは、イオン交換膜支持体、とりわけ蓄電デバイスに好適に用いることができる。
Smart Images

Figure 2026165418000001 
Figure 2026165418000002 
Figure 2026165418000003
Abstract
Description
[Technical Field]
[0001] The present invention relates to a porous film for energy storage device separators, an ion exchange membrane support, and an energy storage device. [Background technology]
[0002] Polymer porous films, which have numerous micro-interconnected pores, are used in a variety of fields, including as separation membranes for the production of ultrapure water, purification of chemical solutions, and water treatment; as waterproof and breathable films for clothing and sanitary materials; and as separators for electronic components such as capacitors, batteries, and electrolytic capacitors.
[0003] In particular, porous films primarily composed of polyolefin resins are used as separators in energy storage devices such as various capacitors, batteries, and electrolytic capacitors. Such porous films, primarily composed of polyolefin resins, are manufactured by methods such as controlling the crystallization of the polyolefin resin during the cooling and solidification process after melt extrusion and then stretching the crystallized polyolefin resin film to create porosity; applying strain, such as stretching, to a polyolefin molded body in which different solids are micro-dispersed to create voids between the different solids and thus create porosity; or micro-dispersing fine powders of different polymers, paraffins, waxes, etc., in a polyolefin resin and then extracting them with a solvent.
[0004] Patent documents 1 to 4 propose a technique for obtaining a stretched porous film by using a polypropylene resin as a matrix, blending a styrene-based thermoplastic elastomer that exhibits partial compatibility with the matrix as domains, melt-extruding it from a T-die, and then melt-solidifying the resulting sheet-like material with a cast roll, followed by biaxial stretching. In these techniques, the porous structure can be adjusted depending on the type of styrene-based thermoplastic elastomer used. Furthermore, Patent Document 5 proposes that a polyolefin microporous membrane having a predetermined film thickness and a specific curvature ratio exhibits excellent isotropy in mass transfer. [Prior art documents] [Patent Documents]
[0005] [Patent Document 1] Japanese Patent Publication No. 2016-141786 [Patent Document 2] Japanese Patent Publication No. 2017-222823 [Patent Document 3] Japanese Patent Publication No. 2015-230743 [Patent Document 4] Japanese Patent Publication No. 2019-199529 [Patent Document 5] Japanese Patent Publication No. 2020-066716 [Overview of the project] [Problems that the invention aims to solve]
[0006] In recent years, there has been a growing demand for thinner films and improved air permeability in porous films. However, during the manufacturing of porous films, due to the metal release properties of the extruded resin, deposits sometimes form around the die lip and other areas. If these deposits drip onto the film during film formation, the film may break during stretching, leading to a decrease in productivity.
[0007] Therefore, the object of the present invention is to provide a porous film for energy storage device separators that can suppress the generation of deposits when manufacturing a porous film, particularly when producing pellets by melt-extruding a resin composition, and by using such pellets, can reduce deposits during film formation, as well as an ion exchange membrane support and an energy storage device using the same. [Means for solving the problem]
[0008] To address these issues, the present invention proposes a porous film for a separator in an energy storage device, an ion exchange membrane support, and an energy storage device according to the following embodiments.
[0009] [1] A first aspect of the present invention is a porous film for a storage device separator, formed from a resin composition [I] mainly composed of a polyolefin resin (A), wherein the porous film contains a metal component (m) derived from a higher fatty acid metal salt (M), and the content of the metal component (m) in the porous film is 0.02 to 2% by mass.
[0010] [2] A second aspect of the present invention is a porous film for a storage device separator, formed from a resin composition [I] mainly composed of a polyolefin resin (A), wherein the resin composition [I] contains a higher fatty acid metal salt (M) containing a metal component (m), and the content of the metal component (m) in the resin composition [I] is 0.02 to 2% by mass.
[0011] [3] A third aspect of the present invention is a porous film for a separator of an energy storage device according to the first or second aspect, wherein the resin composition [I] mainly comprises a polyolefin resin (A) and further contains a styrene thermoplastic elastomer (B). [4] A fourth aspect of the present invention is a porous film for a storage device separator according to any one of the first to third aspects, wherein the melting point of the higher fatty acid metal salt (M) is 90 to 240°C.
[0012] [5] A fifth aspect of the present invention is a porous film for a storage device separator according to any one of the first to fourth aspects, wherein the polyolefin resin (A) is a polypropylene resin. [6] A sixth aspect of the present invention is a porous film for a storage device separator according to any one of the first to fifth aspects, wherein the melt flow rate (MFR(A)) of the polyolefin resin (A) at a temperature of 230°C and a load of 2.16 kg is 1 g / 10 min or more.
[0013] [7] A seventh aspect of the present invention is the porous film for electrical storage device separators according to any one of the third to sixth aspects, wherein the styrene-based thermoplastic elastomer (B) has a melt flow rate (MFR(B)) of 2 g / 10 minutes or less at a temperature of 200°C under a load of 10 kg, the porous film being for electrical storage device separators. [8] An eighth aspect of the present invention is the porous film for electrical storage device separators according to any one of the third to seventh aspects, wherein the content ratio of the styrene-based thermoplastic elastomer (B) relative to the total amount (100 mass%) of the polyolefin-based resin (A) and the styrene-based thermoplastic elastomer (B) is 10 mass% or more and less than 50 mass%, the porous film being for electrical storage device separators.
[0014] [9] A ninth aspect of the present invention is the porous film for electrical storage device separators according to any one of the first to eighth aspects, which has a thickness (T) of 50 μm or less, the porous film being for electrical storage device separators.
[10] A tenth aspect of the present invention is the porous film for electrical storage device separators according to any one of the first to ninth aspects, wherein the resin composition [I] contains a crystal nucleating agent (C), the porous film being for electrical storage device separators.
[0015]
[11] An eleventh aspect of the present invention is an ion exchange membrane support comprising the porous film for electrical storage device separators according to any one of the first to tenth aspects.
[12] A twelfth aspect of the present invention is an electrical storage device comprising the ion exchange membrane support according to the eleventh aspect. [Advantageous Effects of the Invention]
[0016] According to the present invention, when manufacturing a porous film, particularly when producing pellets by melt-extruding a resin composition, the generation of deposits can be suppressed. Furthermore, by using such pellets, deposits during film formation can be reduced, allowing for stable and long-term film production. Moreover, the porous film for energy storage device separators according to the present invention is a thin film that also exhibits good air permeability. Therefore, the porous film for energy storage device separators of the present invention can be suitably used as an ion exchange membrane support, particularly in energy storage devices. [Modes for carrying out the invention]
[0017] A porous film and a method for producing the same, as an example of an embodiment of the present invention, will be described in detail below. However, the scope of the present invention is not limited to the embodiments described below.
[0018] In this invention, "film" includes sheets. Furthermore, in this invention, when "x~y" (where x and y are any numbers) is written, unless otherwise specified, it includes the meaning of "greater than or equal to x and less than or equal to y," as well as the meaning of "preferably greater than x" or "preferably less than y." Furthermore, "greater than or equal to x" (where x is any number) generally means "preferably greater than x" unless otherwise specified, and "less than or equal to y" (where y is any number) generally means "preferably less than y" unless otherwise specified.
[0019] <<The Porous Film of the Invention>> A porous film according to an example of an embodiment of the present invention (hereinafter also referred to as "the porous film of the present invention") is a porous film formed from a resin composition [I] mainly composed of a polyolefin resin (A), and contains a metal component (m) derived from a higher fatty acid metal salt (M). Here, the term "main component" refers to the component with the highest mass percentage among the components constituting the resin composition [I]. The content of the main component can be assumed to be 50% or more by mass, 60% or more by mass, 70% or more by mass, 80% or more by mass, or 90% or more by mass of the components constituting the resin composition [I].
[0020] <Resin composition [I]> The resin composition [I] preferably contains a polyolefin resin (A) as the main component, a higher fatty acid metal salt (M) containing a metal component (m), a styrene-based thermoplastic elastomer (B) if necessary, and preferably further contains additives such as a crystal nucleating agent (C) and an antioxidant if necessary.
[0021] The resin composition [I] forming the porous film of the present invention contains a polyolefin resin (A) as its main component and a higher fatty acid metal salt (M) containing a metal component (m). When the resin composition [I] is melt-extruded, the higher fatty acid metal salt (M) is formed at the interface between the molten resin and metals such as conduits and die caps. This suppresses the generation of deposits at the die cap lip and other parts when pellets are produced by melt-extruding the resin composition. By using pellets with reduced deposits in this way to manufacture films, deposits during film production can be reduced, allowing for stable and long-term film production. Therefore, the porous film of the present invention is a thin film with good air permeability, while still allowing for the production of suitable films.
[0022] The components constituting the resin composition [I] are described in detail below.
[0023] [Polyolefin resin (A)] Examples of polyolefin resins (A) include homopolypropylene (propylene homopolymer), or random copolymers or block copolymers of propylene with α-olefins such as ethylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, or 1-decene. The polyolefin resin (A) exemplified above may be used individually or in combination of two or more types. Among these, homopolypropylene is preferred from the viewpoint of mechanical strength.
[0024] When the polyolefin resin (A) is a polypropylene resin, its isotactic pentad fraction is preferably 80 mol% or more and 99 mol% or less, more preferably 83 mol% or more or 98 mol% or less, and even more preferably 85 mol% or more or 97 mol% or less. The isotactic pentad fraction exhibits stereoregularity, and if the isotactic pentad fraction is too low, sufficient porosity may not be achieved through stretching. On the other hand, the upper limit of the isotactic pentad fraction is currently defined as the upper limit achievable industrially, but this may not apply if resins with even higher regularity are developed at an industrial level in the future. The isotactic pentad fraction refers to the stereostructure or proportion in which five methyl groups in the side chain are all oriented in the same direction relative to a carbon-carbon bonded main chain composed of any five consecutive propylene units. The signal assignment of the methyl group region follows A. Zambelli et al., Macromol., 8, 687 (1975).
[0025] The weight-average molecular weight (Mw) of the polyolefin resin (A) is preferably between 100,000 and 1,000,000, more preferably between 150,000 and 800,000, and even more preferably between 200,000 and 600,000, from the viewpoint of extrusion moldability and mechanical strength.
[0026] The Mw / Mn ratio of the polyolefin resin (A) is preferably 1.5 or more and 10.0 or less, more preferably 2.0 or more or 8.0 or less, and even more preferably 2.5 or more or 6.0 or less. Mw / Mn is a parameter that indicates the molecular weight distribution; a smaller Mw / Mn value means a narrower molecular weight distribution. By setting Mw / Mn above the lower limit, sufficient extrusion moldability can be obtained, making industrial mass production possible. On the other hand, by setting Mw / Mn below the upper limit, sufficient mechanical strength can be ensured. In this invention, the Mw / Mn ratio is a value measured by GPC (gel permeation chromatography).
[0027] The melt flow rate (MFR(A)) of the polyolefin resin (A) at a temperature of 230°C and a load of 2.16 kg is preferably 1 g / 10 min or more. By having a melt flow rate (MFR(A)) of 1 g / 10 min or more, for example, when dispersing a styrene-based thermoplastic elastomer (B), described later, in a polyolefin resin (A), the planar orientation of the styrene-based thermoplastic elastomer (B) can be suppressed, and the dispersion diameter of the styrene-based thermoplastic elastomer (B) becomes larger, thereby improving the communication in the thickness direction, and as a result, the air permeability of the porous film of the present invention can be improved. From this viewpoint, the melt flow rate (MFR(A)) of the polyolefin resin (A) is preferably 1 g / 10 min or more, more preferably 1.5 g / 10 min or more, more preferably 3 g / 10 min or more, more preferably 5 g / 10 min or more, and even more preferably 7 g / 10 min or more. On the other hand, the upper limit is preferably 20 g / 10 min or less, more preferably 18 g / 10 min or less, and even more preferably 16 g / 10 min or less. By keeping the MFR below the above upper limit, the porous film of the present invention can be given sufficient strength. When using two or more polyolefin resins (A) in combination, it is sufficient that at least one of the polyolefin resins (A) has the above-mentioned MFR value. The MFR of the polyolefin resin (A) in this invention was measured in accordance with JIS K7210-1 (2014) under conditions of a temperature of 230°C and a load of 2.16 kg.
[0028] The tensile modulus of polyolefin resin (A) at 23°C is preferably 1000 MPa to 3000 MPa. Since the tensile modulus of the polyolefin resin (A) affects the air permeability and bubble point pressure of the porous film of the present invention, it is preferable that the tensile modulus of the polyolefin resin (A) is within the aforementioned range in order to adjust the air permeability and bubble point pressure of the porous film of the present invention to a predetermined range. From this viewpoint, the tensile modulus of the polyolefin resin (A) at 23°C is preferably 1000 MPa or more, more preferably 1300 MPa or more, and more preferably 1600 MPa or more. On the other hand, it is preferably 3000 MPa or less, more preferably 2700 MPa or less, and more preferably 2400 MPa or less.
[0029] As polyolefin resin (A), commercially available products such as "Novatec PP," "WINTEC," and "Waymax" (manufactured by Nippon Polypropylene Co., Ltd.); "Notio" and "Tafmer XR" (manufactured by Mitsui Chemicals, Inc.); "Zelus" and "Thermoran" (manufactured by Mitsubishi Chemical Corporation); "Sumitomo Noblen" and "Toughselenium" (manufactured by Sumitomo Chemical Co., Ltd.); "Prime PP" and "Prime TPO" (manufactured by Prime Polymer Co., Ltd.); "Adflex," "Adsyl," and "HMS-PP (PF814)" (manufactured by Sun Allomer Co., Ltd.); "Versify" and "Inspire" (manufactured by Dow Chemical Company) can be used.
[0030] The content of polyolefin resin (A) in the resin composition [I] is preferably 50% by mass or more and 95% by mass or less, more preferably 55% by mass or more or 90% by mass or less, even more preferably 60% by mass or more or 85% by mass or less, and particularly even more preferably 70% by mass or less. When the content of polyolefin resin (A) is within the above range, a sea-island structure can be formed with polyolefin resin (A) as the matrix and, for example, styrene-based thermoplastic elastomer (B) as the domain, making it easier to form a porous structure when stretched.
[0031] [Styrene-based thermoplastic elastomer (B)] The resin composition [I], i.e., the porous film of the present invention, preferably further contains a styrene-based thermoplastic elastomer (B). By kneading and melting a styrene-based thermoplastic elastomer (B) with a polyolefin resin (A), the styrene-based thermoplastic elastomer (B) forms a sea-island structure as domains within the matrix of the polyolefin resin (A), thereby obtaining a porous film with a highly uniform porous structure, making it easier to control the shape and diameter of the pores.
[0032] Styrene-based thermoplastic elastomers (B) are a type of thermoplastic elastomer resin based on a styrene component, and are copolymers consisting of a continuum of a soft component (e.g., a butadiene component) and a hard component (e.g., a styrene component). Specifically, some of these copolymers have been hydrogenated to change the double bonds of carbon into single bonds.
[0033] Furthermore, examples of the types of copolymers include random copolymers, block copolymers, and graft copolymers. Examples of block copolymers include linear block structures and radially branched block structures.
[0034] Examples of styrene-based thermoplastic elastomers (B) include styrene-olefin-styrene copolymer (B1) and styrene-olefin copolymer (B2). Examples of styrene-olefin-styrene copolymers (B1) include styrene-butadiene-styrene copolymer (SBS), styrene-butadiene-butylene-styrene copolymer (SBBS), styrene-ethylene-butadiene-styrene copolymer (SEBS), styrene-isoprene-styrene copolymer (SIS), styrene-ethylene-propylene-styrene copolymer (SEPS), and styrene-ethylene-ethylene-propylene-styrene copolymer (SEEPS). Examples of styrene-olefin copolymers (B2) include styrene-butadiene copolymer (SBR), hydrogenated styrene-butadiene copolymer (SEB), styrene-isoprene copolymer (SIR), and styrene-ethylene-propylene copolymer (SEP). The styrene-based thermoplastic elastomer (B) exemplified above may be used individually or in combination of two or more types.
[0035] Among the above, if the compatibility with polyolefin resin (A) is low, a porous structure tends to be formed more easily. Therefore, from the viewpoint of porous structure formation, it is preferable to use a resin having a structure in which both ends are styrene polymers as the main component. On the other hand, in order to efficiently disperse the styrene-based thermoplastic elastomer (B) in the resin composition [I], it is preferable to use a resin containing an ethylene component (hydrogenated butadiene component), an ethylene-propylene component (hydrogenated isoprene component), or a butylene component that has high compatibility with polyolefin resin (A) as the main component. That is, from the viewpoint of porous structure formation, it is preferable to use a styrene-olefin-styrene copolymer (B1) as the main component, from the viewpoint of dispersibility of the styrene-based thermoplastic elastomer (B), it is preferable to use SEP, SEPS, SEBS, or SEEPS as the main component, and from the viewpoint of both above, it is more preferable to use SEPS or SEEPS as the main component, and among these, it is particularly preferable to use SEEPS as the main component. In the context of styrene-based thermoplastic elastomer (B), the "main component" refers to the resin that is most abundant in the resin composition [I] as styrene-based thermoplastic elastomer (B). More specifically, when the total amount of styrene-based thermoplastic elastomer (B) is considered as 100% by mass, the main component refers to the resin that accounts for preferably 50% by mass or more, more preferably 55% by mass or more, and even more preferably 60% by mass or more, with a maximum of 100% by mass.
[0036] Furthermore, from the viewpoint of achieving a higher level of balance between air permeability and mechanical properties, it is preferable that the styrene-based thermoplastic elastomer (B) contained in the resin composition [I] includes styrene-olefin-styrene copolymer (B1) and styrene-olefin copolymer (B2). By combining two or more types of styrene-based thermoplastic elastomers (B), the uniformity of the porous structure obtained by the stretching process can be improved.
[0037] In the porous film of the present invention, pores are formed within the domains of the styrene-based thermoplastic elastomer (B) as starting points for cracking that occurs during stretching. The structure of the domains is closely related to the porous structure, and the larger the domains, the larger the pores and the improved air permeability. Among the styrene-based thermoplastic elastomers (B), styrene-olefin-styrene copolymer (B1) is preferred because it is easier to obtain large domains. Furthermore, the uneven distribution of the styrene-olefin copolymer (B2) on the surface of the domains improves the dispersibility of the domains and enhances the uniformity of the porous structure. Furthermore, within the domain, pores formed by the styrene-olefin copolymer (B2) are formed between the large pores formed by the styrene-olefin-styrene copolymer (B1), thereby improving the communication of the pores and leading to further improvements in air permeability.
[0038] The styrene content in the styrene-based thermoplastic elastomer (B) is preferably 10% by mass or more and less than 50% by mass relative to the total amount (100% by mass) of the polyolefin resin (A) and the styrene-based thermoplastic elastomer (B), and more preferably 20% by mass or more or 45% by mass or less, and more preferably 30% by mass or more or 45% by mass or less, and particularly preferably 35% by mass or more or 40% by mass or less. If the styrene content is above the lower limit, domains can be effectively formed in the polyolefin resin (A), and if the styrene content is below the upper limit, the formation of excessively large domains can be suppressed. Note that if the resin composition [I] contains two or more types of styrene-based thermoplastic elastomers (B), the above styrene content refers to the total amount of styrene-based thermoplastic elastomers (B).
[0039] The weight-average molecular weight (Mw) of the main component resin among the styrene-based thermoplastic elastomer (B) contained in the resin composition [I] is preferably 100,000 or more, more preferably 150,000 or more or 1,000,000 or less, more preferably 800,000 or less, even more preferably 600,000 or less, even more preferably 500,000 or less, even more preferably 400,000 or less, even more preferably 350,000 or less, and particularly preferably 300,000 or less. Furthermore, the Mw / Mn of the main component resin among the styrene-based thermoplastic elastomer (B) contained in the resin composition [I] is preferably 1.00 or more and 1.50 or less, more preferably 1.40 or less, and even more preferably 1.05 or more or 1.20 or less.
[0040] When a film made of a resin composition [I] is stretched in at least one axial direction to create a porous structure, the microstructure (morphology) of the polyolefin resin (A) and styrene thermoplastic elastomer (B) in the resin composition before stretching is one of the factors that influence the formation of the porous structure. Specifically, it is preferable, from the viewpoint of ease of pore formation and other factors, that the styrene thermoplastic elastomer (B), which exists as domains in a matrix mainly composed of the polyolefin resin (A), is spherical, as will be explained below. Generally, when a resin composition having a matrix / domain sea-island structure is melt-extruded and then cooled and solidified, the resin composition extruded from shaping equipment such as a die or nozzle is cooled and solidified using cooling and solidification equipment such as a cast roll (cooling roll), air cooling, or water cooling. In this process, the resin composition melts and expands in the gap between the shaping equipment and the cooling and solidification equipment. Therefore, if the weight-average molecular weight of the styrene-based thermoplastic elastomer (B) domain is small, a resin composition is obtained in which the domains are expanded in the flow direction (extrusion direction). When the domains are expanded in the flow direction (extrusion direction), the area of the domain particles in the flow direction becomes larger, making it less likely for cleavage to occur inside the domains in response to stress in the flow direction (extrusion direction), and a porous structure may not be sufficiently formed. On the other hand, when the weight-average molecular weight of the styrene-based thermoplastic elastomer (B), which is the domain, is large, the domain is less affected by melt elongation, and the domains in the resulting resin composition before stretching tend to remain spherical. When the domains are spherical, cracking is more likely to occur inside the domain in response to stress in the flow direction (extrusion direction), so it is thought that a sufficiently porous structure is formed. For these reasons, it is preferable that the weight-average molecular weight (Mw) of the main component resin in the styrene-based thermoplastic elastomer (B) be within the above range. Furthermore, it is even more preferable that the ratio (molecular weight distribution) Mw / Mn of the number-average molecular weight Mn to the weight-average molecular weight (Mw) of the main component resin in the styrene-based thermoplastic elastomer (B) be within the above range, as this tends to result in a more uniform dispersion diameter of the formed domains.
[0041] The melt flow rate (MFR(B)) of the styrene-based thermoplastic elastomer (B) contained in the resin composition [I], measured at a temperature of 200°C and a load of 10 kg, is preferably 2 g / 10 min or less. The styrene-based thermoplastic elastomer (B) dispersed in the resin composition changes shape depending on the viscosity difference with the polyolefin resin (A). However, if the styrene-based thermoplastic elastomer has an MFR below the above upper limit, it is easier to increase the viscosity difference with the polyolefin resin (A), and the shape tends to become spherical. Spherically dispersed domains tend to have higher uniformity in the porous structure obtained by the subsequent stretching process than domains with a large aspect ratio, making it possible to obtain a porous film with excellent physical stability despite being a thin film. From this viewpoint, the melt flow rate (MFR(B)) is preferably 2 g / 10 min or less, more preferably 1 g / 10 min or less, more preferably 0.5 g / 10 min or less, and even more preferably 0.1 g / 10 min or less. The lower limit is not particularly limited, but it is usually 0g / 10min, i.e., a non-flowing state. When using two or more types of styrene-based thermoplastic elastomers (B), it is sufficient that at least one of the styrene-based thermoplastic elastomers (B) has the above-mentioned MFR value. In particular, styrene-based thermoplastic elastomers with an MFR within the above range are preferred if they are the main component of the domain-forming components, as this makes it easier for stress to concentrate inside the domains during the stretching process, thus easily creating pore initiations and leading to porosity. The "main component" refers to the component with the highest mass percentage among the domain-forming components. The content of the main component can be assumed to be 50% or more by mass, 60% or more by mass, 70% or more by mass, 80% or more by mass, or 90% or more by mass of the domain-forming components. The MFR of the styrene-based thermoplastic elastomer (B) in this invention was measured in accordance with JIS K7210-1 (2014) under conditions of a temperature of 200°C and a load of 10 kg.
[0042] In the resin composition [I], the difference (MFR(A)-MFR(B)) between the melt flow rate (MFR(A)) of the polyolefin resin (A) at a temperature of 230°C and a load of 2.16 kg and the melt flow rate (MFR(B)) of the styrene thermoplastic elastomer (B) at a temperature of 200°C and a load of 10 kg is preferably 1 g / 10 min or more. In recent years, there has been a demand for thinner porous films and improved air permeability. However, thinning and air permeability are mutually exclusive properties, and the thinner the film, the worse the air permeability becomes. More specifically, when obtaining porous films with a thickness of 50 μm or less, and especially 30 μm or less, it has been difficult to achieve an air permeability of 10 seconds / 100 mL or less. In view of the above problems, the inventors conducted diligent studies and, by adjusting the combination of polyolefin resin and styrene-based thermoplastic elastomer, as well as the film formation conditions, found that in formulations where the melt flow rates (MFRs) of the polyolefin resin and styrene-based thermoplastic elastomer are significantly different, extremely good air permeability characteristics can be maintained, especially when the film thickness is reduced. When manufacturing the porous film of the present invention, the domains are easily stretched in the MD direction when the film is drawn onto the cast, and pores are formed when the styrene-based thermoplastic elastomer is stretched in the MD direction, with the styrene-based thermoplastic elastomer acting as the starting point. In this case, when the domains are stretched in the MD direction, stress is less likely to concentrate in the domains, making it difficult to form pores. It is thought that if the difference in melt flow rate (MFR) between the polyolefin resin and the styrene-based thermoplastic elastomer is large, the dispersion diameter of the styrene-based thermoplastic elastomer domains that serve as the starting point for openings will increase, and deformation of the domains in the in-plane direction will be suppressed, resulting in improved communication in the thickness direction and reduced air permeability. From the above viewpoint, the difference (MFR(A)-MFR(B)) between the melt flow rate (MFR(A)) of the polyolefin resin (A) and the melt flow rate (MFR(B)) of the styrene thermoplastic elastomer (B) is preferably 1 g / 10 min or more, more preferably 3 g / 10 min or more, more preferably 5 g / 10 min or more, and more preferably 7 g / 10 min or more. Furthermore, from the viewpoint of film formation properties, the difference (MFR(A)-MFR(B)) is preferably 20 g / 10 min or less, and more preferably 15 g / 10 min or less. If the resin composition [I] contains two or more polyolefin resins (A) and / or two or more styrene-based thermoplastic elastomers (B), the MFR(A) value shall be the difference between the polyolefin resin (A) with the highest MFR(A) value and the styrene-based thermoplastic elastomer (B) with the lowest MFR(B) value.
[0043] In the resin composition [I], the content ratio of the styrene-based thermoplastic elastomer (B) to the total amount (100% by mass) of the polyolefin-based resin (A) and the styrene-based thermoplastic elastomer (B) is preferably 10% by mass or more and less than 50% by mass, more preferably 12% by mass or more or 45% by mass or less, and even more preferably 15% by mass or more or 40% by mass or less. When the content of styrene-based thermoplastic elastomer (B) is within the above range, a sea-island structure can be formed with polyolefin resin (A) as the matrix and styrene-based thermoplastic elastomer (B) as the domains, making it easier to form a porous structure when stretched.
[0044] [Metal components (m) derived from higher fatty acid metal salts (M)] In this invention, "higher fatty acid" means a fatty acid that contains 10 or more carbon atoms in its molecule. Examples of "higher fatty acids" in the higher fatty acid metal salt (M) include stearic acid, oleic acid, lauric acid, capric acid, arachidic acid, palmitic acid, behenic acid, 12-hydroxystearic acid, ricinoleic acid, and montanic acid. However, it is not limited to these. Among these, behenic acid, 12-hydroxystearic acid, and montanic acid are preferred from the viewpoint of thermal stability. On the other hand, examples of metal salts for higher fatty acid metal salts (M) include alkaline earth metal salts such as magnesium salts, calcium salts, and barium salts; alkali metal salts such as sodium salts, potassium salts, and lithium salts; cadmium salts; zinc salts; and lead salts. However, the examples are not limited to these. Among these, barium salts and zinc salts are preferred from the viewpoint of lubricity when compounded with resin.
[0045] Specific examples of higher fatty acid metal salts (M) include, for example, magnesium stearate, magnesium laurate, magnesium palmitate, magnesium 12-hydroxystearate, calcium stearate, calcium oleate, calcium laurate, calcium 12-hydroxystearate, barium stearate, barium oleate, barium laurate, barium arachidinate, barium behenate, barium 12-hydroxystearate, zinc stearate, zinc oleate, zinc laurate, zinc 12-hydroxystearate, lithium stearate, lithium 12-hydroxystearate, sodium stearate, sodium palmitate, sodium laurate, sodium 12-hydroxystearate, potassium stearate, potassium laurate, calcium montanate, and aluminum 12-hydroxystearate. However, the list is not limited to these. In particular, barium 12-hydroxystearate and zinc 12-hydroxystearate are preferred from the viewpoint of thermal stability and lubricity during resin compounding.
[0046] The content of the metal component (m) in the higher fatty acid metal salt (M) is preferably 0.02 to 2% by mass, more preferably 0.03% or more by mass or 1% or less by mass, and more preferably 0.04% or more by mass or 0.5% or less by mass, in terms of thermal stability and lubricity when compounded with resin.
[0047] The melting point of the higher fatty acid metal salt (M) is preferably 90°C to 240°C in terms of thermal stability, and more preferably 110°C or higher or 220°C or lower, and more preferably 130°C or higher or 200°C or lower. From the viewpoint of having a melting point of 90°C to 240°C, preferred higher fatty acid metal salts (M) include, for example, barium 12-hydroxystearate and zinc 12-hydroxystearate.
[0048] From the viewpoint of lubricity during resin compounding, the content of the metal component (m) in the resin composition [I] is preferably 0.02% by mass or more, more preferably 0.03% by mass or more, more preferably 0.035% by mass or more, and more preferably 0.04% by mass or more. On the other hand, from the viewpoint of dispersibility, it is preferably 2% by mass or less, more preferably 1% by mass or less, more preferably 0.5% by mass or less, and more preferably 0.25% by mass or less. The content of metal component (m) in the resin composition [I] can be calculated by decomposing the resin composition [I] with nitric acid at 70-220°C and performing ICP analysis on the solution at specific wavelengths for each metal component. However, this method is not the only one that can be used.
[0049] [Crystal Nucleating Agent (C)] The resin composition [I] preferably contains a nucleating agent (C) because increasing the rigidity of the polyolefin resin (A) is considered effective in void formation when creating porosity by stretching between the polyolefin resin (A) and the styrene thermoplastic elastomer (B).
[0050] The content of the nucleating agent (C) is preferably 0.001 parts by mass or more and 10 parts by mass or less per 100 parts by mass of the total amount of the resin components in the resin composition [I], i.e., the polyolefin resin (A) and the styrene thermoplastic elastomer (B), more preferably 0.005 parts by mass or more or 5 parts by mass or less, even more preferably 0.01 parts by mass or more or 2 parts by mass or less, and even more preferably 0.05 parts by mass or more or 1.5 parts by mass or less.
[0051] As the nucleating agent (C), α-nucleating agents and β-nucleating agents are preferred, with α-nucleating agents being preferred from the viewpoint of excellent heat resistance. On the other hand, β-nucleating agents are preferred from the viewpoint of thermal fusion properties.
[0052] Examples of α-nucleating agents that can be used include dibenzylidenesorbitol (manufactured by Shin-Nippon Rika Co., Ltd., trade name "Gelol MD"), "ADEKA Stab NA-11", "ADEKA Stab NA-27", "ADEKA Stab NA-902", "ADEKA Stab NA-21", and "ADEKA Stab NA-71" (all five of the above manufactured by ADEKA Corporation), a masterbatch containing a mixture of magnesium stearate and silica (manufactured by Dainichi Seika Kogyo Co., Ltd., trade name "High Cycle Master"), and a masterbatch containing the sodium salt of 2-hydroxy-2-oxo-4,6,10,12-tetra-tert-butyl-1,3,2-dibenzo[d,g]perhydrodioxaphosphalosine (manufactured by ADEKA Corporation, trade name "ADEKA Stab M-701").
[0053] Other α-nucleating agents include, as inorganic nucleating agents, silica, talc, and calcium carbonate. Organic nucleating agents (carboxylate metal salt type) include, for example, calcium stearate, sodium benzoate, aluminum benzoate, aluminum dibenzoate, potassium benzoate, lithium benzoate, sodium β-naphthalate, sodium cyclohexane carboxylate, metal pimephosphate, and metal rosinate. Benzylidene sorbitol and its derivatives, as well as phosphate ester metal salts, are also available. Furthermore, polymer types include, for example, poly-3-methylbutene-1, polyvinylcycloalkane, polyvinyltrialkylsilane, EPR, Kevlar® fiber, and sodium 2,2'-methylenebis(4,6-di-tert-butylphenyl)phosphate.
[0054] The content of the α-nucleating agent in the resin composition [I] is preferably 0.001 parts by mass or more and 10 parts by mass or less per 100 parts by mass of the total amount of the resin components in the resin composition [I], i.e., the polyolefin resin (A) and the styrene thermoplastic elastomer (B), more preferably 0.005 parts by mass or more or 5 parts by mass or less, even more preferably 0.01 parts by mass or more or 2 parts by mass or less, and even more preferably 0.05 parts by mass or more or 1.5 parts by mass or less. If the α-nucleating agent content is above the lower limit mentioned above, sufficient α-crystal formation can be achieved. On the other hand, if the α-nucleating agent content is below the upper limit mentioned above, there is no risk of α-nucleating agent bleeding, plate-out, or powder shedding during the film formation process or secondary processing process, and this is preferable in terms of lower costs.
[0055] Examples of β-crystal nucleating agents include amide compounds; tetraoxaspiro compounds; quinacridones; nanoscale iron oxides; alkali or alkaline earth metal salts of carboxylic acids, such as potassium 1,2-hydroxystearate, magnesium benzoate or magnesium succinate, or magnesium phthalate; aromatic sulfonic acid compounds, such as sodium benzenesulfonate or sodium naphthalenesulfonate; or di or triesters of tribasic carboxylic acids; phthalocyanine pigments, such as phthalocyanine blue; two-component compounds consisting of component A, which is an organic dibasic acid, and component B, which is an oxide, hydroxide, or salt of a Group IIA metal in the periodic table; and compositions consisting of cyclic phosphorus compounds and magnesium compounds. Furthermore, specific types of nucleating agents are described in Japanese Patent Publication No. 2003-306585, Japanese Patent Publication No. 06-289566, and Japanese Patent Publication No. 09-194650.
[0056] Examples of commercially available β-nucleating agents include "NJester NU-100" manufactured by Shin Nippon Rika Co., Ltd., and specific examples of polypropylene with added β-nucleating agents include "BepolB-022SP" from Aristech, "Beta(β)-PPBE60-7032" from Borealis, and "BNXBETAPP-LN" from Mayzo.
[0057] The β-nucleating agent is preferably blended into the polyolefin resin (A). In this case, the ratio of the β-nucleating agent to the polyolefin resin (A) is preferably adjusted as appropriate depending on the type of β-nucleating agent or the composition of the polyolefin resin (A). From this viewpoint, the content of the β-nucleating agent is preferably 0.0001 to 5.0 parts by mass per 100 parts by mass of the total amount of the resin components, i.e., the polyolefin resin (A) and the styrene-based thermoplastic elastomer (B), more preferably 0.001 parts by mass or more or 3.0 parts by mass or less, and even more preferably 0.01 parts by mass or more or 1.0 part by mass or less. If the content of the β-crystal nucleating agent is above the lower limit, sufficient β-crystals of the polyolefin resin (A) can be generated and grown during manufacturing, ensuring sufficient β-crystal activity and obtaining the desired air permeability performance when used as an ion exchange membrane support. Furthermore, if the content is below the upper limit, it is economically advantageous and preferable as it does not result in bleeding of the β-crystal nucleating agent onto the surface of the porous film. Furthermore, if layers containing polyolefin are laminated in addition to the resin layer made of polyolefin resin (A), the amount of β-nucleating agent added to each layer may be the same or different. By changing the amount of β-nucleating agent added, the porous structure of each layer can be adjusted as appropriate.
[0058] [Other ingredients] The resin composition [I] may contain various additives, such as antioxidants, heat stabilizers, ultraviolet absorbers, light stabilizers, colorants, antistatic agents, hydrolysis inhibitors, lubricants, and flame retardants, to an extent that does not impair its properties. It may also contain other resins to an extent that does not impair its properties. Furthermore, the resin composition [I] can be subjected to surface treatments such as corona treatment, plasma treatment, printing, coating, vapor deposition, and perforation, as necessary, without impairing the present invention, and several layers of the porous film of the present invention can be used depending on the application.
[0059] <Porous film of the present invention> The porous film of the present invention preferably contains a metal component (m) derived from a higher fatty acid metal salt (M) within the porous film. The porous film of the present invention contains a metal component (m) derived from a higher fatty acid metal salt (M), or in other words, a higher fatty acid metal salt (M) containing a metal component (m). When the resin composition is melt-extruded to produce pellets, the higher fatty acid metal salt (M) is formed at the interface between the molten resin and metals such as conduits and die caps. This suppresses the generation of deposits at the die cap lip and other parts when the resin composition is melt-extruded. Furthermore, by using pellets with reduced deposits, deposits can be reduced during film formation. Thus, the porous film of the present invention is a thin film with good air permeability, while still allowing for the production of suitable films.
[0060] The content of the metal component (m) in the porous film of the present invention is preferably 0.02% by mass or more from the viewpoint of lubricity when compounded with resin, more preferably 0.03% by mass or more, more preferably 0.035% by mass or more, and more preferably 0.04% by mass or more. On the other hand, from the viewpoint of porous properties and mechanical strength, it is preferably 2% by mass or less, more preferably 1% by mass or less, more preferably 0.5% by mass or less, and more preferably 0.25% by mass or less. The content of metal components (m) in the porous film can be calculated by performing ICP analysis on a solution obtained by decomposing the porous film with nitric acid at 70-220°C, using specific wavelengths for each metal component. However, this is not the only method.
[0061] The porous film of the present invention may be formed solely of a porous layer made of the above resin composition, or other layers may be laminated to the extent that they do not impede the features of the present invention.
[0062] (Thickness) The thickness (T) of the porous film of the present invention is preferably 50 μm or less. A thickness (T) of 50 μm or less contributes to the thinning and high integration of the cell stack when the porous film of the present invention is used as an ion exchange membrane support in an energy storage device. On the other hand, the lower limit of the thickness (T) of the porous film of the present invention is preferably 1 μm or more, in order to maintain sufficient strength as a film. From this viewpoint, the thickness (T) of the porous film of the present invention is preferably 50 μm or less, more preferably 1 μm or more or 30 μm or less, even more preferably 2 μm or more or 25 μm or less, and even more preferably 5 μm or more or 20 μm or less.
[0063] (Air permeability (S)) The air permeability (S) of the porous film of the present invention is preferably less than 10 seconds / 100cc, more preferably 9 seconds / 100cc or less, even more preferably 8 seconds / 100cc or less, and even more preferably 7 seconds / 100cc or less. The lower limit is usually 0.25 seconds / 100cc. In this invention, the air permeability (S) is measured under conditions of 25°C in accordance with JIS P8117:2009. To reduce the air permeability (S) of the porous film of the present invention, the porosity of the interconnecting pores should be increased and the diameter of the interconnecting pores should be enlarged. To achieve this, for example, methods include increasing the viscosity difference (e.g., the difference in MFR) between the polyolefin resin (A) and the styrene thermoplastic elastomer (B) to enlarge the pore diameter, using a polyolefin resin (A) with a relatively low molecular weight to enlarge the pore diameter, or adjusting the film thickness. In addition, it can also be adjusted by conditions such as the casting temperature and stretching ratio during film formation. However, it is not limited to these methods.
[0064] (Bubble point pressure) The bubble point pressure (P) of the porous film of the present invention BA The pressure is preferably between 5 kPa and 80 kPa. The bubble point pressure of a film is determined by immersing the film in a liquid with low surface tension, such as alcohol, injecting air from the top or bottom of the film, and gradually increasing the pressure until the first bubble appears. The bubble point pressure of a film is proportional to the surface tension of the liquid and inversely proportional to the pore diameter, and therefore correlates with the largest pore in the film, i.e., the maximum pore diameter. For details on the method for measuring the bubble point pressure of the porous film of the present invention, please refer to the measurement method in the examples. While a larger maximum pore diameter in the porous film of the present invention can improve air permeability, if it is too large, it can cause problems such as tearing if the film is thin. From this viewpoint, in order to adjust the maximum pore diameter of the porous film of the present invention to a preferred range, the corresponding bubble point pressure is preferably 5 kPa or more, more preferably 8 kPa or more, more preferably 11 kPa or more, and more preferably 14 kPa or more. On the other hand, from the viewpoint of air permeability, it is preferably 80 kPa or less, more preferably 75 kPa or less, more preferably 70 kPa or less, and more preferably 65 kPa or less. The bubble point pressure of the porous film of the present invention can be adjusted, for example, by the chemical structure, molecular weight, MFR, tensile modulus, and content of the polyolefin resin (A), the chemical structure, molecular weight, MFR, and content of the styrene-based thermoplastic elastomer (B), as well as the casting temperature and stretching ratio during film formation. However, it is not limited to these.
[0065] (Maximum pore diameter) In the porous film of the present invention, the maximum pore diameter is preferably 0.5 μm or more and 9.0 μm or less. The maximum pore diameter is determined by the bubble point pressure (P) BA This is the maximum pore diameter calculated from ). As described above, while a larger maximum pore diameter in the porous film of the present invention can improve air permeability, if it is too large, it can cause problems such as tearing when the film is thin. Therefore, the maximum pore size of the porous film of the present invention is preferably 0.5 μm or more, more preferably 1.0 μm or more, still more preferably 1.5 μm or more, and even more preferably 2.0 μm or more. On the other hand, it is preferably 9.0 μm or less, more preferably 7.0 μm or less, still more preferably 5.0 μm or less, and even more preferably 3.0 μm or less.
[0066] (S / P BA ) Of the porous film of the present invention, the ratio (S / P of air permeability (S) (sec / 100cc) and bubble point pressure (P BA ) (kPa) BA ), that is, the ratio (S / P of the air permeability (S) (sec / 100cc) of the porous film of the present invention to the bubble point pressure (P BA ) (kPa) BA ) correlates with the film thickness and porosity, and a smaller ratio (S / P BA ) is preferable because the film tends to have a smaller thickness and a higher porosity. From this viewpoint, the ratio (S / P of the porous film of the present invention BA ) is preferably 0.5 sec / (100cc·kPa) or less, more preferably 0.4 sec / (100cc·kPa) or less, still more preferably 0.3 sec / (100cc·kPa) or less, and even more preferably 0.2 sec / (100cc·kPa) or less. The lower limit is usually 0.003 sec / (100cc·kPa) from the viewpoints of film thickness and porosity. In the porous film of the present invention, the ratio (S / P BA ) can be adjusted by, for example, the chemical structures, molecular weights, MFRs, and contents of the polyolefin-based resin (A) and the styrene-based thermoplastic elastomer (B), the casting temperature during film formation, the stretching ratio, and the like. However, the adjustment method is not limited to these methods.
[0067] (S / T) Of the porous film of the present invention, the ratio (S / T) of air permeability (S) (sec / 100cc) and thickness (T) (μm), that is, the ratio (S / T) of the air permeability (S) (sec / 100cc) to the thickness (T) (μm) is preferably 0.5 sec / (100cc·μm) or less. A ratio of air permeability (S) to thickness (T) (S / T) of 0.5 seconds / (100cc·μm) or less allows for the creation of a porous film with excellent air permeability characteristics, even in a thin film (e.g., 50μm or less). On the other hand, the lower limit is 0.01 seconds / (100cc·μm) from the viewpoint of pore size and porosity. From this viewpoint, the (S / T) value is preferably 0.5 seconds / (100cc·μm) or less, and more preferably 0.45 seconds / (100cc·μm) or less, more preferably 0.40 seconds / (100cc·μm) or less, more preferably 0.35 seconds / (100cc·μm) or less, and more preferably 0.30 seconds / (100cc·μm) or less. On the other hand, from the viewpoint of pore size and porosity, it is preferably 0.01 seconds / (100cc·μm) or more, and more preferably 0.02 seconds / (100cc·μm) or more, more preferably 0.03 seconds / (100cc·μm) or more, more preferably 0.04 seconds / (100cc·μm) or more, and more preferably 0.05 seconds / (100cc·μm) or more. The (S / T) value can be adjusted, for example, by the chemical structure, molecular weight, MFR, content, casting temperature during film formation, and stretching ratio of the polyolefin resin (A) and styrene thermoplastic elastomer (B). However, the method is not limited to these.
[0068] (porosity) The porous film of the present invention preferably has a porosity of 50% or more, more preferably 55% or more, and more preferably 60% or more. The upper limit of the porosity is not particularly limited, but it is practical to have a value of 90% or less. To adjust the porosity of the porous film of the present invention to the above range, for example, it can be adjusted by the chemical structure, molecular weight, MFR, tensile modulus, and content of the polyolefin resin (A), the chemical structure, molecular weight, MFR, and content of the styrene-based thermoplastic elastomer (B), as well as the casting temperature and stretching ratio during film formation. If the porous film of the present invention has layers other than the porous layer, it is sufficient that the porosity of only the porous layer be within the above range. The porosity is the sum of the porosity of the connected and non-connected pores, and can be calculated from the density of the resin composition using the method described in the examples.
[0069] (MD tensile modulus) The porous film of the present invention preferably has a tensile modulus of 25 MPa or more at 23°C in the flow direction (MD). The porous film of this invention has a tensile modulus of 25 MPa or more at 23°C in the flow direction (MD), which makes it less likely for wrinkles to form on the roll when the film is wound into a roll. From this viewpoint, the tensile modulus of the porous film of the present invention at 23°C in the flow direction (MD) is preferably 25 MPa or higher, more preferably 30 MPa or higher, more preferably 35 MPa or higher, and more preferably 40 MPa or higher. There is no particular upper limit, but for example, a limit of 500 MPa or less can be considered. The tensile modulus of the porous film of the present invention at 23°C can be adjusted by the molecular weight, melting point, MFR, content, stretching conditions, etc., of the polyolefin resin (A) and styrene thermoplastic elastomer (B).
[0070] (MD storage modulus) The porous film of the present invention preferably has a storage modulus (E') of 1 MPa or more at 150°C and 10 Hz in the flow direction (MD). If the storage modulus (E') of the porous film of the present invention at 150°C and 10Hz in the flow direction (MD) is 1 MPa or higher, it can be said to have heat resistance. From this viewpoint, it is preferable that the storage modulus (E') of the porous film of the present invention at 150°C and 10Hz in the flow direction (MD) is 1 MPa or more, more preferably 3 MPa or more, more preferably 5 MPa or more, and more preferably 7 MPa or more. There is no particular upper limit, but for example, a value of 100 MPa or less can be considered. The MD storage modulus of the porous film of the present invention at 150°C and 10Hz can be adjusted by the molecular weight, melting point, MFR, content, stretching conditions, etc., of the polyolefin resin (A) and the styrene-based thermoplastic elastomer (B).
[0071] (Average tensile strength) The average tensile strength of the porous film of the present invention is preferably 2 MPa or higher. The porous film of the present invention can be made to have excellent mechanical properties by having an average tensile strength of 2 MPa or more. From this viewpoint, the average tensile strength of the porous film of the present invention is more preferably 4 MPa or more, more preferably 6 MPa or more, more preferably 8 MPa or more, and even more preferably 10 MPa or more. The upper limit is not particularly limited, but may be, for example, 400 MPa or less, 300 MPa or less, 200 MPa or less, or 100 MPa or less. The porous film of the present invention is preferable because its average tensile strength is below the upper limit, resulting in excellent handling properties. In this invention, the average tensile strength is the average value of the tensile strengths in the MD and TD measured by the method described in the examples. If the MD and TD are unknown, the average value of the tensile strength in any length direction and the width direction perpendicular thereto may be used.
[0072] (Average tensile strength at break) The average tensile elongation at break of the porous film of the present invention is preferably 1% or more, more preferably 10% or more, even more preferably 20% or more, and even more preferably 30% or more. There is no particular upper limit, but it may be, for example, 200% or less. By having the average tensile elongation at break of the porous film of the present invention be within the above range, excellent mechanical properties can be obtained. In this invention, the average tensile elongation at break is the average value of the tensile elongations at MD and TD measured by the method described in the examples. If MD and TD are unknown, the average value of the tensile elongations at break in any length direction and the width direction perpendicular thereto may be used.
[0073] The average tensile strength and average tensile elongation at break can be adjusted by the chemical structure, molecular weight, MFR, content, casting temperature during film formation, and stretch ratio of the polyolefin resin (A) and styrene thermoplastic elastomer (B). For example, the average tensile strength and average tensile elongation at break can be adjusted by: using a styrene-based thermoplastic elastomer (B) with low compatibility with a polyolefin resin (A) as the main component; using a resin with a high weight-average molecular weight (Mw) as the main component of the styrene-based thermoplastic elastomer (B); using a resin with a low MFR (i.e., high viscosity) as the styrene-based thermoplastic elastomer (B); adjusting the content ratio of the polyolefin resin (A) and the styrene-based thermoplastic elastomer (B) to the above-mentioned suitable range; adjusting the temperature of the cast roll during film formation to the suitable range in the manufacturing method described later; and, in the case of biaxial stretching, adjusting the longitudinal and transverse stretching magnifications and stretching ratios to the suitable range. Applying the methods exemplified above will not only control the morphology of the polyolefin resin (A) and the styrene thermoplastic elastomer (B), but will also lead to the formation of porous structures and control of film thickness. Therefore, it is thought that an appropriate porous structure will be formed, leading to improved air permeability.
[0074] <Method for manufacturing a porous film according to the present invention> The present invention's method for producing a porous film (hereinafter also referred to as "this method") preferably comprises the steps of: melt-extruding a resin composition [I] mainly composed of a polyolefin resin (A) and containing a higher fatty acid metal salt (M), preferably a resin composition [I] mainly composed of a polyolefin resin (A) and further containing a styrene-based thermoplastic elastomer (B) and a higher fatty acid metal salt (M), to produce pellets; further melt-extruding the pellets to obtain an unstretched sheet; and stretching the unstretched sheet to obtain a porous film (II).
[0075] [Process (I)] First, in step (I), under temperature conditions above the melting point of the polyolefin resin (A) and below the decomposition temperature, a resin composition [I], such as a polyolefin resin (A), a styrene-based thermoplastic elastomer (B), a higher fatty acid metal salt (M), and a crystal nucleating agent (C), is melted and kneaded using an extruder or the like to produce pellets. These pellets are then melt-extruded to form a sheet, thereby obtaining a non-porous sheet before stretching. In this case, a twin-screw extruder can be used to produce the pellets, for example, and a strand die can be used as the nozzle at the end. Furthermore, one possible method for forming non-porous sheets is T-die molding.
[0076] When forming the kneaded material into a sheet while cooling it, the temperature of the cast roll is preferably 60°C to 150°C, more preferably 70°C to 140°C, even more preferably 80°C to 130°C, and even more preferably 90°C to 120°C. When the temperature of the cast roll is above the lower limit, the crystallization of the polyolefin resin (A) proceeds sufficiently, and a porous structure is fully formed. On the other hand, when the temperature of the cast roll is below the upper limit, problems such as the unstretched sheet fusing with the roll and breaking are less likely to occur.
[0077] The speed of the cast roll is preferably 1.0 m / min or more and 5.0 m / min or less, more preferably 1.2 m / min or more and 4.0 m / min or less, and even more preferably 1.5 m / min or more and 3.0 m / min or less. By setting the cast roll speed above the lower limit mentioned above, productivity improves. On the other hand, by setting the cast roll speed below the upper limit mentioned above, it becomes easier to maintain the spherical shape of the domains in the sheet before stretching, and a sufficiently porous structure is formed after stretching.
[0078] [Process (Ia)] In this manufacturing method, step (I) may include a step (Ia) in which the resin composition is melt-extruded into a sheet and brought into contact with the cast roll, thereby bringing the sheet into contact with the cast roll. Specifically, examples include a touch roll, pinning, and touch rollers at both ends in the width direction of the sheet.
[0079] By ensuring the sheet is in close contact with the cast roll, uneven adhesion is minimized, which in turn suppresses uneven pore formation in the stretched film, resulting in a porous film with uniform properties.
[0080] [Process (II)] Next, the resulting pre-stretched sheet is subjected to uniaxial or biaxial stretching. Uniaxial stretching may be vertical uniaxial stretching or horizontal uniaxial stretching. Biaxial stretching may be simultaneous biaxial stretching or sequential biaxial stretching.
[0081] To produce the permeable porous film of the present invention, one can select the stretching conditions at each stretching step, and it is more preferable to employ sequential biaxial stretching, which allows for easier control of the porous structure. Furthermore, stretching a sheet in the direction of flow (MD) is called "longitudinal stretching," while stretching it perpendicular to the direction of flow (TD) is called "lateral stretching."
[0082] When sequential biaxial stretching is used, the control of the porous structure is relatively easy, and it is easier to balance it with other physical properties such as mechanical strength and shrinkage rate. Furthermore, the stretching temperature can be appropriately selected depending on the composition of the resin composition used, the crystal melting peak temperature, the degree of crystallinity, etc.
[0083] Longitudinal stretching is preferably carried out at a low temperature, and the specific stretching temperature is preferably 0 to 50°C, more preferably 5°C or higher or 40°C or lower. If the longitudinal stretching temperature is below the upper limit mentioned above, stress tends to concentrate inside the domain during stretching, making it easier for voids to form. On the other hand, if the longitudinal stretching temperature is above the lower limit mentioned above, it is preferable because it can suppress fracture during stretching.
[0084] The longitudinal stretching (MD) ratio at low temperatures is preferably 1.1 to 5.0 times, more preferably 1.2 times or more or 4.5 times or less, and even more preferably 1.3 times or more or 4.0 times or less. By setting the stretching ratio at low temperatures to above the lower limit, pore formation progresses, suggesting that sufficient porosity is achieved through stretching. Furthermore, by setting the stretching ratio at low temperatures to below the upper limit, fracture during stretching can be suppressed.
[0085] Furthermore, the longitudinal stretching (MD) may be a two-stage stretching process in which stretching at a high temperature follows the stretching at a low temperature as described above. The specific high-temperature stretching temperature is preferably 60 to 155°C, more preferably 70°C or higher or 140°C or lower, and even more preferably 80°C or higher or 130°C or lower. By setting the longitudinal stretching temperature at high temperatures above the lower limit mentioned above, film rupture during stretching can be suppressed. On the other hand, by setting the longitudinal stretching temperature at high temperatures below the upper limit mentioned above, it is possible to suppress the closure of pores formed by stretching at low temperatures.
[0086] The longitudinal stretching (MD) ratio at high temperatures is preferably 1.0 to 5.0 times, more preferably 1.2 times or more or 4.5 times or less, even more preferably 1.3 times or more or 4.0 times or less, and even more preferably 1.5 times or more or 3.0 times or less. By setting the stretching ratio at high temperatures to be above the lower limit, the pores formed by longitudinal stretching at low temperatures can be enlarged. Furthermore, by setting the stretching ratio at high temperatures to be below the upper limit, the film's properties (thickness, air permeability, and mechanical properties) can be adjusted to a suitable range, and film breakage during stretching can be suppressed.
[0087] The temperature for transverse stretching (TD) is preferably 100 to 170°C, more preferably 110°C or higher, or 160°C or lower. By keeping the transverse stretching temperature within the above range, the voids created during longitudinal stretching can be enlarged, increasing the porosity of the porous layer, and allowing it to have sufficient air permeability and mechanical properties.
[0088] The transverse stretching (TD) ratio can be selected arbitrarily, but is preferably 1.1 to 10 times, more preferably 1.5 times or more or 8.0 times or less, and even more preferably 2.0 times or more or 6.0 times or less. By stretching at the above transverse stretching ratio, it is possible to achieve a sufficient porosity without deforming the voids created during longitudinal stretching.
[0089] Furthermore, when producing the porous film of the present invention by biaxial stretching, it is preferable to set the stretching ratio of longitudinal stretching to transverse stretching to longitudinal:transverse = 0.5 to 2.0:1, and more preferably to set it to 0.7 to 1.5:1. By keeping the stretching ratio within the above range, the film's properties (thickness, air permeability, and mechanical properties) can be adjusted to a suitable range. Furthermore, if longitudinal stretching is performed in two stages, at low and high temperatures, the lateral stretching ratio should be within the range specified above (longitudinal stretching ratio at low temperature × longitudinal stretching ratio at high temperature).
[0090] <Application> The porous film of the present invention can be used in various fields, such as separation membranes used in the production of ultrapure water, purification of chemical solutions, and water treatment; waterproof and breathable films used in clothing and sanitary materials; and separators used in electronic components such as capacitors, batteries, and electrolytic capacitors. In particular, the porous film of the present invention can be suitably used for energy storage device separators, and especially as a support for the ion exchange membrane therefor.
[0091] (Ion exchange membrane support) The porous film of the present invention is useful as an ion exchange membrane support. That is, the ion exchange membrane support of the present invention is made of the porous film of the present invention. Preferred embodiments and preferred properties of the ion exchange membrane support of the present invention are the same as those described for the porous film.
[0092] (Energy storage device) The energy storage device of the present invention preferably comprises the ion exchange membrane support of the present invention described above. Examples of energy storage devices include lithium secondary batteries such as redox flow batteries, nickel-metal hydride batteries, lithium metal secondary batteries, lithium-ion secondary batteries, lithium polymer secondary batteries, and lithium-ion polymer secondary batteries, as well as capacitor-type devices such as aluminum electrolytic capacitors, electric double-layer capacitors, and lithium-ion capacitors. Among these, redox flow batteries and lithium secondary batteries are preferred. [Examples]
[0093] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the following examples unless it exceeds the gist of the invention.
[0094] <Material> (Polyolefin resin (A)) (A-1) Homopolypropylene (weight-average molecular weight (Mw): 254,300, molecular weight distribution (Mw / Mn): 5.03, MFR(A) (230℃, 2.16kg): 10g / 10min, tensile modulus at 23℃: 2050MPa) The above tensile modulus is the value obtained by measuring it using a tensile testing machine in accordance with JIS K7161 and JIS K7162. The above MFR(A) value was measured in accordance with JIS K7210-1 (2014) under conditions of a temperature of 230°C and a load of 2.16 kg.
[0095] (Styrene-based thermoplastic elastomer (B)) (B-1) Styrene-ethylene-ethylene-propylene-styrene block copolymer (SEEPS) (Weight-average molecular weight (Mw): 196,000, Molecular weight distribution (Mw / Mn): 1.07, MFR (230℃, 2.16kg): Non-flowing, MFR(B) (200℃, 10kg): Non-flowing, Styrene content: 32% by mass) The above MFR(B) values were measured in accordance with JIS K7210-1 (2014) under conditions of a temperature of 200°C and a load of 10 kg.
[0096] (Higher fatty acid metal salt (M)) (M-1) Zinc 1,2-hydroxystearate, Metal component (m): Zn (zinc), Metal content: 9.0-10.0%, Melting point: 145-155°C, Acid value: Maximum 3.0 (M-2) 1,2-Barium hydroxystearate, Metal component (m): Ba (barium), Metal content: 17.0-19.0%, Melting point: 161-178°C, Acid value: Maximum 2.0
[0097] (Cell nucleating agent (C)) (C-1) β-nucleating agent (3,6-bis[4-(N-cyclohexylcarbamoyl)phenyl]-2,4,8,10-tetraoxaspiro[5.5]undecane)
[0098] (Antioxidant (D)) (D-1) Phosphorus-based antioxidant (3,9-bis(2,6-di-tert-butyl-4-methylphenoxy)-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane) (D-2) Phenolic antioxidant (3,9-bis[2-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy]-1,1-dimethylethyl]-2,4,8,10-tetraoxaspiro[5.5]undecane)
[0099] (External lubricant (E)) (E-1) Stearamide, melting point: 100-105°C, oxidation state: 2 or less (E-2) Ultra-high molecular weight silicone (manufactured by Asahi Kasei Wacker Silicone Co., Ltd., product name: GENIOPLAST PELLET S)
[0100] <Preparation of porous film> In Example 1 and Comparative Example 1, pellets and porous films were prepared.
[0101] (Example 1) A polyolefin resin (A-1) was blended in a ratio of 60 parts by mass to 40 parts by mass to styrene-based thermoplastic elastomer (B-1). To the total of 100 parts by mass of the polyolefin resin (A-1) and styrene-based thermoplastic elastomer (B-1), a crystal nucleating agent (C-1) was added in a ratio of 0.05 parts by mass, an antioxidant (D-1) in a ratio of 0.1 parts by mass to (D-2), and a higher fatty acid metal salt (M-1) in a ratio of 0.5 parts by mass. The mixture was then fed into a twin-screw extruder, melt-kneaded at a set temperature of 230°C, and the molten resin was extruded using a strand die to produce pellets, i.e., full compound pellets (samples). Here, the content of metal components contained in the pellets (resin composition) was as shown in Table 1.
[0102] Next, the prepared pellets were fed into a φ65 mm single-screw extruder, melted and kneaded at a set temperature of 205°C, and then formed into a sheet using a T-die. The sheet was then placed on a cast roll set to the conditions shown in the table and cooled and solidified to obtain a pre-stretched sheet with a thickness of 95 μm. Subsequently, the obtained unstretched sheet was subjected to low-temperature stretching at the magnification ratio shown in the table between a roll (X) set to 25°C and a roll (Y) also set to 25°C to obtain an MD stretched porous film. Next, the obtained MD stretched porous film was preheated at a preheating temperature of 145°C in a film tenter, then stretched transversely at a stretching temperature of 145°C at the magnification ratio shown in the table, heat-treated at 155°C, and wound up on a winding machine to obtain a porous film (sample).
[0103] Up to 30 minutes after the start of full compound pellet preparation, almost no eye discharge was observed on the nozzle lip of the strand die. Furthermore, the entire process from the start of porous film production (i.e., feeding the pellets into the single-screw extruder) to its completion (i.e., the end of winding) took approximately 300 minutes. During this time, almost no deposit buildup was observed in the T-die, and no film breakage due to deposit buildup was observed. The content of metal components (m) contained in the pellets (resin composition) and porous film was as shown in Table 1.
[0104] (Comparative Example 1) In Example 1, the process was carried out in accordance with Example 1, except that the higher fatty acid metal salt (M-1) was omitted and the cast roll temperature was changed to 98°C, to obtain pellets (sample) and porous film (sample). Thirty minutes after the start of full compound pellet preparation, a significant amount of eye discharge was observed adhering to the lip of the strand die nozzle. Approximately 60 minutes after the start of porous film production, film rupture due to deposits generated by the T-die was observed, and continuous production for more than 60 minutes thereafter was not possible. The content of metal components (m) contained in the pellets (resin composition) and porous film was as shown in Table 1.
[0105] <Pellet preparation> In Example 2 and Comparative Examples 2 and 3, the process was carried out up to the pellet preparation stage.
[0106] (Example 2) In Example 1, the procedure was carried out in accordance with Example 1, except that the higher fatty acid metal salt (M-1) was changed to the higher fatty acid metal salt (M-2) shown in Table 1, to prepare a full compound pellet (sample). During pellet preparation, the effect of reducing eye discharge was evaluated in the same manner as in Example 1. Here, the content of metal components contained in the pellets (resin composition) was as shown in Table 2.
[0107] (Comparative Example 2) In Example 1, the procedure was carried out in accordance with Example 1, except that the higher fatty acid metal salt (M-1) was replaced with the external lubricant (E-1) shown in Table 1, to prepare a full compound pellet (sample). During pellet preparation, the effect of reducing eye discharge was evaluated in the same manner as in Example 1. Here, the content of metal components contained in the pellets (resin composition) was as shown in Table 2.
[0108] (Comparative Example 3) In Example 1, the procedure was carried out in accordance with Example 1, except that the higher fatty acid metal salt (M-1) was replaced with the external lubricant (E-2) shown in Table 1, to prepare a full compound pellet (sample). During pellet preparation, the effect of reducing eye discharge was evaluated in the same manner as in Example 1. Here, the content of metal components contained in the pellets (resin composition) was as shown in Table 2.
[0109] <Evaluation Method> For each example, the content of metal components (m) in the pellets (resin composition) was measured, and the effect of reducing eye discharge during pellet production was evaluated as follows. Furthermore, for Example 1 and Comparative Example 1 described above, the content of metal components (m) in the porous film was measured, and the performance of the film was also evaluated.
[0110] (1) Measurement of the content of metal components (m) in pellets (resin composition) or porous film The pellets or porous films obtained in each example and comparative example were decomposed with nitric acid at 70°C using a microwave apparatus, as shown in the following table, and the content of metal components (m) in the resulting solutions was measured by ICP analysis under the conditions shown in the table.
[0111] TIFF2026165418000001.tif85170
[0112] For the analysis, the concentration X (mg / L) of each metal (m) was obtained by comparing the measured intensity at the wavelength of each metal (m) with the calibration curve. From this concentration X, the content (wt%) in the sample (pellet or porous film) was calculated using the following formula.
[0113] TIFF2026165418000002.tif25170
[0114] (2) Evaluation of reduction in eye discharge As described in each example and comparative example, the effect of reducing eye deposits during pellet production was evaluated as follows. In addition, in Example 1 and Comparative Example 1, the presence or absence of eye deposit generation at the T-die during film formation was also observed. During the production of full compound pellets, the adhesion of eye discharge to the nozzle lip and other parts of the strand die was observed. The adhesion of eye discharge was then evaluated according to the following criteria, compared to immediately after extrusion. ◎(Best)...Almost no eye discharge was observed. ○(Good) ···A slight amount of eye discharge was observed. × (Bad) ...There was a lot of eye discharge.
[0115] (3) Thickness (film thickness) (T) A 10cm square was cut from the porous film (sample), and measurements were taken at 9 points using a dial gauge with a scale of 1 / 1000mm. The average value of these measurements was used as the thickness.
[0116] (4) Bubble point pressure (P BA ) and average flow rate diameter pressure (P Ap ) Using a palm porometer (Porous Materials), and using the polyhexafluoropropene liquid "GALWICK" (Porous Materials, surface tension: 15.6 dynes / cm) as the reagent, the bubble point pressure (P) of the porous film (sample) was measured in accordance with ASTM F316-86. BA ) was measured. Bubble point pressure (P BA The wet flow curve, dry flow curve, and half-dry flow curve are shown on the graph, and the average flow diameter pressure (P) is taken from the intersection of the wet flow curve and the half-dry flow curve. Ap ) was sought.
[0117] (5) Maximum pore diameter The aforementioned bubble point pressure (P BA Using the following formula, the maximum pore diameter d of the porous film (sample) was determined. d = cγ / P c: constant 2860 γ: Surface tension of the liquid "GALWICK": 15.6 dynes / cm P: Pressure P at the bubble point BA
[0118] (6) Air permeability (S) The air permeability resistance of a porous film (sample) was measured in an air atmosphere at 25°C, in accordance with JIS P8117:2009. A digital Ouken-type dedicated air permeability analyzer (manufactured by Asahi Seiko Co., Ltd.) was used as the measuring instrument.
[0119] (7) Porosity A porous film (sample) was cut into 10 cm squares, its density ρ1 (apparent density) was measured, and its density ρ0 (true density) was calculated when the porosity was 0%. From these values, the porosity was calculated based on the following formula. Porosity (%)=(1-ρ1 / ρ0)×100
[0120] (8) Tensile strength, tensile elongation at fracture The measuring device used was a tensile testing machine (Shimadzu Corporation AG-1kNXplus). The test specimen was a rectangle cut from a porous film (sample) with a length of 60 mm and a width of 10 mm in the measurement direction. Both ends of the test specimen in the longitudinal direction were chucked with a chuck distance of 20 mm, and the specimen was pulled at a crosshead speed of 200 mm / min. The strength at the maximum point from the start of the test until fracture was measured as the tensile strength, and the elongation at fracture was measured as the tensile elongation at fracture. Three measurements were taken, and the average value was calculated. The above tensile tests were performed on both the median diameter (MD) and tensile transverse diameter (TD) of the film. In addition, the average tensile strength and average tensile elongation at fracture were calculated by averaging the MD and TD values for tensile strength and tensile elongation at fracture, respectively. The measurements were performed at room temperature (25°C).
[0121] (9) Tensile modulus The measuring device used was a tensile testing machine (AGS-X tensile testing machine manufactured by Shimadzu Corporation). The test specimen was a rectangle cut from a porous film (sample) with a length of 150 mm and a width of 10 mm in the measurement direction. Both ends of the test specimen in the longitudinal direction were chucked with a chuck distance of 100 mm, and the tensile modulus was determined by pulling at a crosshead speed of 5 mm / min. Three measurements were performed, and the average value was calculated. The above tensile tests were performed on both the median diameter (MD) and tectonic plate (TD) of the film. The average tensile modulus was calculated by averaging the MD and TD values for each. The measurements were performed at room temperature (25°C).
[0122] (10) Storage modulus (E') A dynamic viscoelasticity measuring device (DVA-200, manufactured by IT Measurement Control Co., Ltd.) and a tensile jig were used to measure the storage modulus (E') of porous films (samples) at 150°C under the conditions of a measurement temperature of 30-200°C, a strain of 0.1%, a frequency of 10 Hz, and a heating rate of 3°C / min. The table shows the storage modulus (E') of the porous films (samples) at 150°C. For MD measurements, a sample with an MD gauge length of 2 cm and a TD width of 0.4 cm was used, and for TD measurements, a sample with a TD gauge length of 2 cm and an MD width of 0.4 cm was used.
[0123] (11) Manufacturing Life The manufacturing life was defined as the time (in minutes) from when the formed film was started to be wound on the winding machine until it broke.
[0124] [Table 1]
[0125] [Table 2]
[0126] In addition, when calculating "MFR(A)-MFR(B)" in Tables 1 and 2, substances that "did not flow" during MFR measurement were calculated with an MFR value of 0.
[0127] (Consideration) As shown in Tables 1 and 2, it was confirmed that the generation of deposits during pellet production could be suppressed in Examples 1 and 2. Furthermore, in Example 1, it was confirmed that deposits during film formation could be reduced by using pellets with reduced deposits. As a result, it was confirmed that the manufacturing life could be extended and productivity could be improved. Furthermore, as shown in Table 1, in Example 1, despite being a thin film, the air permeability and bubble point pressure (P) were excellent. BA It was confirmed that a film with excellent maximum pore diameter and mechanical properties can be obtained, that is, a porous film that is thin yet possesses good air permeability and mechanical properties, and has a long manufacturing life. On the other hand, in the comparative example, which did not contain a higher fatty acid metal salt (M) containing a metal component (m), or which contained such a metal component (m) but in an amount of less than 0.02% by mass, it was confirmed that eye discharge occurred in the nozzle lip area and other parts when the pellets were manufactured. In particular, Comparative Example 1 showed a low effect in reducing eye discharge and had a short manufacturing life during film formation.
[0128] By including a metal component (m) derived from a higher fatty acid metal salt (M), a mechanism of action can be obtained in which the higher fatty acid metal salt (M) is expressed at the interface between the molten resin and metals such as conduits and die fittings during melt extrusion. As shown in the examples, it is possible to suppress the generation of deposits at the die fitting lip and other parts when producing pellets by melt extrusion of the resin composition, while maintaining thin film and good air permeability. Furthermore, by using pellets with reduced deposits in this way, it is possible to suppress the generation of deposits at T-dies and other parts during film formation, reducing the frequency of breakage as deposits are less likely to drip onto the film, thereby improving film productivity.
[0129] Furthermore, based on the above examples and comparative examples, as well as the test results conducted by the inventors to date, the air permeability (S) of the porous film formed from the resin composition [I] mainly composed of polyolefin resin (A) is set to less than 10 seconds / 100cc, and the bubble point pressure (P) is set to less than 10 seconds / 100cc. BA It was found that by setting the pressure between 5 and 80 kPa, the air permeability characteristics can be further improved even when the film thickness is reduced, specifically to 50 μm or less. Furthermore, it was found that even when forming a porous film from a resin composition [I] mainly composed of a polyolefin resin (A), the tensile modulus at 23°C in the flow direction (MD) is set to 30 MPa or higher, the porosity to 80% or lower, and the air permeability (S) to less than 10 seconds / 100cc, a porous film with good air permeability characteristics can be obtained, even when the film is thin and has stiffness. Furthermore, it was found that in a porous film formed from a resin composition [I] mainly composed of polyolefin resin (A), the storage modulus (E') at 150°C and 10Hz in the flow direction (MD) is 1 MPa or higher, and the air permeability (S) is less than 10 seconds / 100cc, thereby improving both heat resistance and air permeability.
Claims
1. A porous film for energy storage device separators, formed from a resin composition [I] mainly composed of a polyolefin resin (A), wherein the porous film contains a metal component (m) derived from a higher fatty acid metal salt (M), and the content of the metal component (m) in the porous film is 0.02 to 2% by mass.
2. A porous film for energy storage device separators, formed from a resin composition [I] mainly composed of a polyolefin resin (A), wherein the resin composition [I] contains a higher fatty acid metal salt (M) containing a metal component (m), and the content of the metal component (m) in the resin composition [I] is 0.02 to 2% by mass.
3. The porous film for a power storage device separator according to claim 1 or 2, wherein the resin composition [I] mainly comprises a polyolefin resin (A) and further contains a styrene-based thermoplastic elastomer (B).
4. The porous film for a battery storage device separator according to claim 1 or 2, wherein the melting point of the higher fatty acid metal salt (M) is 90 to 240°C.
5. The porous film for a power storage device separator according to claim 1 or 2, wherein the polyolefin resin (A) is a polypropylene resin.
6. The porous film for a storage device separator according to claim 1 or 2, wherein the melt flow rate (MFR(A)) of the polyolefin resin (A) at a temperature of 230°C and a load of 2.16 kg is 1 g / 10 min or more.
7. The porous film for a storage device separator according to claim 3, wherein the melt flow rate (MFR(B)) of the styrene-based thermoplastic elastomer (B) at a temperature of 200°C and a load of 10 kg is 2 g / 10 min or less.
8. The porous film for a battery storage device separator according to claim 3, wherein the content ratio of the styrene-based thermoplastic elastomer (B) to the total amount (100% by mass) of the polyolefin resin (A) and the styrene-based thermoplastic elastomer (B) is 10% by mass or more and less than 50% by mass.
9. A porous film for a battery storage device separator according to claim 1 or 2, wherein the thickness (T) is 50 μm or less.
10. The porous film for a storage device separator according to claim 1 or 2, wherein the resin composition [I] contains a nucleating agent (C).
11. An ion exchange membrane support comprising a porous film for a storage device separator according to claim 1 or 2.
12. An energy storage device comprising an ion exchange membrane support as described in claim 11.
Citation Information
Patent Citations
Separator for power storage device and power storage device
JP2015230743A
Polypropylene-based resin porous body and separator for electronic member and electronic member using the same
JP2016141786A
Method for producing stretched porous film
JP2017222823A
Drawing porous film
JP2019199529A
Polyolefin microporous film, filter, chromatography carrier, and strip for immunochromatography
JP2020066716A